Climate change science : a primer for sustainable development - Mutter, John C. (Columbia University Earth Institute sustainability primers., 2020)
"How will future climates be different from today's world-and what consequences will changes in climate have for societies and their development strategies? This book is a primer on the essential science for grasping the workings of climate change and climate prediction. John C. Mutter gives an overview of how the climate system functions and what we know about why changes occur. He recounts the evolution of climatology from the earliest discoveries about Earth's climate to present-day predictive capabilities, and clearly presents the scientific basis of fundamental topics such as climate zones, ocean-atmosphere dynamics, and the long-term cycles from glacial to interglacial periods. Mutter also details the mechanisms of climate change and the ways in which human activity affects global climate. He explains the science behind some known consequences of rising temperatures, such as sea level rise, hurricane behavior, and climate variability. The primer discusses how climate predictions are made and examines the sources of uncertainty in forecasting"--